The size distribution of monetary policy effects among South African manufacturing firms: Firm-level evidence from administrative tax data - Keagile Lesame (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Monetary policy is believed to have a disproportionate effect on firms, depending on their size. Financially constrained firms with limited access to capital markets are expected to be more sensitive to changes in interest rates; this is characteristic of small firms. This paper empirically tests this hypothesis for firms in the South African manufacturing sector, using the South African Revenue Service's comprehensive tax administrative data set. The interest coverage ratio is used to measure firms' debt service burden, thus capturing the effect of changes in interest rates on the debt burden of firms categorized by size. The results provide evidence to support the argument that the effect of monetary policy decisions on manufacturing firms depends on firm size: smaller firms experience greater effects of interest rate changes. These findings suggest that monetary authorities should consider the balance sheet health of firms, particularly small firms, when making monetary policy decisions.
Keywords: E0; E4; E5; 330; credit channel; firm heterogeneity; financial constraints; monetary policy; SARS administrative tax database; South Africa